2010
DOI: 10.1093/protein/gzq099
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the molecular determinants of ligand-binding-induced macromolecular switching using thermodynamic cycles

Abstract: The energetic networks that govern regulated switching processes in macromolecules are poorly understood at a molecular level. We illustrate a general methodology that uses thermodynamic cycles to measure the coupling energetics between specific groups in a macromolecule and ligand-binding-induced macromolecular switching. The approach is applied to new and published thermodynamic stability and/or binding data not previously analyzed in this way, for a wide range of switching systems, including H+ or Ca²+-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We then analyzed the contributions of individual residues to switching, using a combination of experimental measurements and atomistic simulations for mutant proteins. In previous experiments, we found that the switch in hisactophilin is broken in the triple myristoyl binding pocket mutant, F6L/I85L/I93L, such that the myristoyl group remains in the sequestered state and does not switch to the accessible state with decreasing pH (25) (Fig. 3C).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…We then analyzed the contributions of individual residues to switching, using a combination of experimental measurements and atomistic simulations for mutant proteins. In previous experiments, we found that the switch in hisactophilin is broken in the triple myristoyl binding pocket mutant, F6L/I85L/I93L, such that the myristoyl group remains in the sequestered state and does not switch to the accessible state with decreasing pH (25) (Fig. 3C).…”
Section: Resultsmentioning
confidence: 70%
“…Based on previous analyses of the pH dependence of stability and NMR data, switching from the sequestered state to the accessible state is caused by the binding of approximately 1.5 protons by a small number of histidine residues localized on one side of the protein (6,25). Also, the protonation of the histidines is coupled to the state of nearby hydrophobic residues including F6, I85 and I93, which sensitively communicate pH changes to the myristoyl binding pocket as evidenced by switching being abolished in the F6L/I85L/I93L (25) and I85L (Fig. 3C) mutants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of such conditions frequently irreversibly damages the protein reagent and/or the target molecule of interest or is simply not compatible with the reaction/assays of interest. Consequently, the development of protein molecular switches,2, 3 which are proteins whose function (e.g., binding) may be modulated (or linked) through an environmental trigger (e.g., pH or ligand) or conformational change, are desired in many applications.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the pH-dependent catalysis helps in identifying the favorable electrostatic interactions which build up the environment for facilitating the catalytic reaction. Knowledge of the residues that govern various pH-dependent functions could allow us to re-engineer these functions 21 which have several industrial and pharmaceutical applications [22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%